PERSONALIZED NANOMEDICINE APPROACHES ENABLED BY BIOINFORMATICS AND MACHINE LEARNING - Zhang Li; Chen Mei; Wang Jing (Journal of Biomedical and Techno Nanomaterials, 2026)
Personalized nanomedicine has emerged as a promising approach to tailor treatments to individual patients, enhancing therapeutic efficacy while minimizing side effects. The integration of bioinformatics and machine learning (ML) has the potential to revolutionize this field by enabling more precise and efficient drug delivery systems, biomarker identification, and therapeutic strategies. However, the full potential of these technologies in personalized nanomedicine remains underexplored. This study aims to explore how bioinformatics and machine learning can enable personalized nanomedicine approaches, particularly in the areas of drug delivery optimization, patient-specific treatment planning, and biomarker discovery. The research investigates the application of these technologies in identifying individualized treatment strategies and improving patient outcomes. A systematic review of the current literature on bioinformatics, machine learning, and personalized nanomedicine was conducted. Case studies and experimental research using these technologies were analyzed to identify trends, applications, and challenges. Machine learning models were applied to bioinformatics datasets to predict drug responses and optimize nanomedicine formulations. The study found that bioinformatics and ML significantly enhance the accuracy of drug efficacy predictions, biomarker identification, and the design of personalized nanomedicine treatments. Furthermore, these technologies have improved patient-specific therapy optimization in clinical trials. The combination of bioinformatics and machine learning holds great promise for advancing personalized nanomedicine, offering tailored therapeutic solutions that improve patient outcomes and treatment efficiency.